Colonic Carcinoma Masquerading as Scrotal Swelling: A Case Report and Review of Literature. (2007) - Paravastu, Sharath C. V.; Batra, Meenakshi; Ananthakrishnan, Krishnan
Abstract : Tumours of the spermatic cord are rare. Most tumours of the spermatic cord are metastatic and are typically an incidental finding at orchidectomy for other pathology. Primary pathology is usually from the gastrointestinal tract. We report a very rare presentation of an asymptomatic gastrointestinal tumour as a spermatic cord mass. male patient presented with a painless scrotal swelling. Radical orchidectomy revealed an adenocarcinoma in the spermatic cord. Further investigations disclosed an adenocarcinoma of the descending colon, metastasing to the spermatic cord that gave a false notion of a scrotal swelling secondary to infection. This unusual situation reminds us that spermatic cord metastases are rare. In the event of nonresponding scrotal swelling to antibiotics, further investigations would be prudent, whilst awaiting the definitive pathology report from the radical orchidectomy.